Value of Bronchial Reversibility to Salbutamol, Exhaled Nitric Oxide and Responsiveness to Methacholine to Corroborate the Diagnosis of Asthma in Children - Mallol-Villablanca, E; Aguirre-Camposano, V; Gallardo-Fernandez, A; Riquelme-Baez, C; Sanchez-Villa, C (Elsevier Doyma, 2020)
Introduction and Objectives: Functional and inflammatory measures have been recommended to corroborate asthma diagnosis in schoolchildren, but the evidence in this regard is conflicting. We aimed to determine, in real-life clinical situation, the value of spirometry, spirometric bronchial reversibility to salbutamol (BDR), bronchial responsiveness to methacholine (MCT) and fractional exhaled nitric oxide (FENO), to corroborate the diagnosis of asthma in children on regular inhaled corticosteroids (ICS) referred from primary care. Methods: One hundred and seventy-seven schoolchildren with mild-moderate persistent asthma, on treatment with regular ICS, participated in the study. Abnormal tests were defined as FENO ≥ 27 ppb, BDR (FEV1 ≥ 12%) and methacholine PC20 ≤ 4 mg/mL. Results: The proportions of positive BDR, FENO and MCT, were 16.4%, 33.3%, and 87.0%, respectively. MCT was associated with FENO (p < 0.03) and BDR (p = 0.001); FENO was associated with BDR (p = 0.045), family history of asthma (p = 0.003) and use of asthma medication in the first two years of life (p = 0.004). BDR was significantly related with passive tobacco exposure (p = 0.003). Conclusions: Spirometry, BDR and BDR had a poor performance for corroborating diagnosis in our asthmatic children on ICS treatment; on the contrary, MCT was positive in most of them, which agrees with previous reports. Although asthma tests are useful to corroborate asthma when positive, clinical diagnosis remains the best current approach for asthma diagnosis, at least while better objective and feasible measurements at the daily practice are available. At present, these tests may have a better role for assessing the management and progression of the condition. © 2020 SEICAP